The evolution of physical and technical performance parameters in the Chinese Soccer Super League - Zhou, Changjing; Gómez, Miguel-Ángel; Lorenzo, Alberto (Biology of Sport, 2020)
Performance analysis in soccer has attained greater importance for coaching staff in order to gather and manage useful information (i.e., physical, technical, and tactical) of their teams during consecutive seasons. Accordingly, we examined the evolution of physical and technical performance parameters in the Chinese Soccer Super League (CSL). Data were collected from 1,429 CSL matches from the 2012 season to the 2017 season using the Amisco Pro (Amisco, Nice, France) system. Fourteen technical performance-related indicators and 11 physical performance-related indicators were analysed using a mixed linear model for repeated measures. Significant main effects of season were followed up using the Bonferroni correction (multiple comparisons). Although there were some irregularities, performance variables generally showed significant upward trends across the six seasons (p<0.05), resulting in significant increases from the 2012 season to the 2017 season in the total sprint distance (2,069.7±509.3 m vs. 2,272±493.6 m; p<0.001; effect size [ES]: 0.40), number of sprints (100.1±22.8 vs. 104.8±20.8, p<0.001; ES: 0.22), high-speed distance (2568.4±503.5 m vs. 2823.1±479.2 m; (p<0.001; ES: 0.52), and high-speed effort (187.5±36.1 to 204.7±33.7; p<0.001; ES: 0.49). Furthermore, there were ~23% more crosses (p<0.001; ES: 0.45), ~12% more shots on target (p<0.001; ES: 0.22), and ~11% more opponent penalty area entries (p<0.001; ES: 0.20) during the 2017 season than in the 2012 season. Coaches and sports scientists should be mindful of this evolution when preparing training sessions and recruiting new players, and even when predicting future trends in the Chinese Soccer Super League.